2015
DOI: 10.1021/acsami.5b05757
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Tension Effect on Cell Partition in Aqueous Two-Phase Systems

Abstract: Aqueous two-phase systems (ATPS) provide a mild environment for the partition and separation of cells. We report a combined experimental and theoretical study on the effect of interfacial tension of polymeric ATPS on the partitioning of cells between two phases and their interface. Two-phase systems are generated using polyethylene glycol and dextran of specific properties as phase-forming polymers and culture media as the solvent component. Ultralow interfacial tensions of the solutions are precisely measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 48 publications
2
76
0
Order By: Relevance
“…10,17,20 mESCs microprinted onto a confluent layer of PA6 cells remained partitioned within the DEX phase drop due to an ultralow interfacial tension between the aqueous PEG and DEX phases. 19,21 mESCs adhered to the stromal layer within 3 hrs of incubation (Fig 1a–b). 19,21 The layer of mitotically inactive PA6 cells remained intact and viable during the 2-week culture period while mESCs rapidly proliferated and formed individual colonies (Fig 1c).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…10,17,20 mESCs microprinted onto a confluent layer of PA6 cells remained partitioned within the DEX phase drop due to an ultralow interfacial tension between the aqueous PEG and DEX phases. 19,21 mESCs adhered to the stromal layer within 3 hrs of incubation (Fig 1a–b). 19,21 The layer of mitotically inactive PA6 cells remained intact and viable during the 2-week culture period while mESCs rapidly proliferated and formed individual colonies (Fig 1c).…”
Section: Resultsmentioning
confidence: 94%
“…19,21 mESCs adhered to the stromal layer within 3 hrs of incubation (Fig 1a–b). 19,21 The layer of mitotically inactive PA6 cells remained intact and viable during the 2-week culture period while mESCs rapidly proliferated and formed individual colonies (Fig 1c). A density of 500 cells per drop resulted in uniformly-sized colonies of 2.0±0.3mm in average diameter on day 8 of culture, irrespective of type of culture vessel.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…It was sometimes reported that the logarithmic value of  for ATPS has a linear relation to the logarithmic tie line length (l tl in wt%) of the phase diagram [14,15]. The relation depends on the degrees of polymerization of the polymers.…”
Section: Estimation Of  For the Atps Interfacementioning
confidence: 99%